Factor Analysis of Practical Cybersecurity Learning Through Gamified Visual Novel Platform - Kevin Alexander; Amril Syalim (Faculty of Computer Science Universitas Indonesia, 2026)
A method of applying game elements in non-game media is known as gamification. This method is often used for learning environments to enhance learners' motivation. Gamification can be applied to any range of game genres, such as visual novel, a narrative-focused game that needs the user to interact and engage. In this research, ARCS (Attention, Relevance, Confidence, Satisfaction) questionnaire was employed to identify key factors that affect learner motivation during practical learning activities in a course focusing on cyber security topics. The Exploratory Factor Analysis (EFA) was utilized to uncover the underlying structure that affects the students' motivation. Through factor analysis, three key factors that influence the students' motivation were found. The first factor involves the students' feelings while using the gamification platform. The second is related to the learning experience of the students. Lastly, the third pertains to how confident the students are in conducting the activities on the gamification platform.